The squeezed middle : the pressure on ordinary workers in America and Britain / edited by Sophia Parker. - Parker, Sophia (Policy, 2013)
The Squeezed Middle brings together leading experts from both sides of the Atlantic to ask what the UK can learn from the US experience of stagnating wages and rising living costs.